Amaranth proteins emulsions as delivery system of Angiotensin-I converting enzyme inhibitory peptides. (May 2019) - Suárez, Santiago; Añón, María Cristina
Abstract: We analyze the possibility of using the emulsifying properties of amaranth proteins and the bioactivity shown by peptide sequences encrypted in these proteins to formulate functional emulsions with angiotensin I-converting enzyme (ACE) inhibitory activity. For this we formulate O:W emulsions, 20:80, from a mixture in equal parts (50:50) of amaranth protein isolates (API), and hydrolysates (AH) at 1 and 2% protein w/v. Results obtained showed that these emulsions, API50-AH50-1% and API50-AH50-2%, are highly flocculated (Flocculation index: 8.2 and 5.9) and stable at least for 8 days, without evident creaming or coalescence. The components present in the emulsions were capable of inhibiting ACE, in in vitro assays (IC50 of 0.14 ± 0.02 mg/mL). API and API50-AH50 emulsions were subjected to a simulated gastrointestinal digestion in vitro . The emulsions were susceptible to aggregation and coalescence phenomena during this process, which could be a consequence of the chaotropic action of the bile salt on the interface and the proteolytic and lipolytic action of pancreatin and lipase, respectively (D4.3 of original emulsion: 1.22 ± 0.01 μm and D4.3 of digested emulsion 79.5 ± 17.1 μm). We also found that amaranth proteins were more resistant to gastric than duodenal digestion. After the process of simulated gastrointestinal digestion, the inhibition of ACE (IC50 of 0.13 ± 0.07 mg/mL) was maintained. This fact evidences the protective effect of the emulsion on the bioavailability of the ACE inhibitory peptides, by either their participation in the formation of the interfacial film and/or their participation in the network of formed flocs. Graphical abstract: Image 1 Highlights: Emulsions using a mixture of native and hydrolyzed amaranth proteins as tensioactive-stabilising agent were obtained. API and API50-AH50 emulsions were subjected to a simulated digestion process. API50-AH50 emulsions were more sensitive to destabilization processes during simulated digestion than API emulsions. AH and API50-AH50 digested emulsions were able to inhibit the angiotensin-converting enzyme. The inhibition of ACE was confirmed after subjected the emulsion API50-AH50 to a simulated digestion process.